COVID‐19 associated pulmonary aspergillosis. Issue 6 (15th May 2020) - Koehler, Philipp; Cornely, Oliver A.; Böttiger, Bernd W.; Dusse, Fabian; Eichenauer, Dennis A.; Fuchs, Frieder; Hallek, Michael; Jung, Norma; Klein, Florian; Persigehl, Thorsten; Rybniker, Jan; Kochanek, Matthias; et al.
Summary: Objectives: Patients with acute respiratory distress syndrome (ARDS) due to viral infection are at risk for secondary complications like invasive aspergillosis. Our study evaluates coronavirus disease 19 (COVID‐19) associated invasive aspergillosis at a single centre in Cologne, Germany. Methods: A retrospective chart review of all patients with COVID‐19 associated ARDS admitted to the medical or surgical intensive care unit at the University Hospital of Cologne, Cologne, Germany. Results: COVID‐19 associated invasive pulmonary aspergillosis was found in five of 19 consecutive critically ill patients with moderate to severe ARDS. Conclusion: Clinicians caring for patients with ARDS due to COVID‐19 should consider invasive pulmonary aspergillosis and subject respiratory samples to comprehensive analysis to detect co‐infection.